Future Book(s) : Sharing ideas on books and (art) publishing - Pol, Pia; Vostermans, Astrid (Amsterdam : Valiz, 2023)
Graphic design by : Arngaard, Line ; Klement, Elisabeth ; van Meel, Dymfy ; Paeva, Victoria ; Pappa, Laura ; Schröder, Lotte Lara ; Stracuzzi, Irene ; Kostelanská, Zuzana
What is the future of the book? And, specifically, what is the future of books on art, design and architecture, and cultural-critical publications? We asked a large number of international interested individuals to respond to this question. Journalists, artists, architects, curators, translators, designers, philosophers, sociologists, teachers, book scholars, publishers, printing houses, distributors, booksellers, historians and art-historians, critics, policymakers,editors, students, and many others have enthusiastically shared their views with us, looking ahead five, twenty or seventy-two years (to the year 2100). At times utopian, wildly fantasizing, at other times with realistic scenarios, in both text and images, exciting for anyone who loves books and/or is involved in books and cultural content. Each section of this publication will be designed by various young designers, to celebrate its scope and diversity.(from publisher)
boek